Blowup Analysis for a Nonlocal Diffusion Equation with Reaction and Absorption - Yulan Wang; Zhaoyin Xiang; Jinsong Hu (Journal of Applied Mathematics)
We investigate a nonlocal reaction diffusion equation with absorption under Neumann boundary. We obtain optimal conditions on the exponents of the reaction and absorption terms for the existence of solutions blowing up in finite time, or for the global existence and boundedness of all solutions. For the blowup solutions, we also study the blowup rate estimates and the localization of blowup set. Moreover, we show some numerical experiments which illustrate our results.